FABRICATION AND CHARACTERIZATION OF POLYETHERSULFONE (PES) MEMBRANES BY BLENDING POLYMERS FOR REMOVAL OF ORGANIC COMPOUNDS IN AIR - Br Sembiring, Nava Resi; Ramadani, Devi; Fathanah, Umi; Sofyana (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2024)
The PES membrane was modified using a polymer blending method to improve the performance and characteristics of the membrane. This research aims to see the effect of adding biosilica additives on the performance characteristics of PES membranes and determine the optimal composition of additives and solvents for making membranes. The membrane was made using the Non-solvent Induced Phase Separation (NIPS) method with a composition consisting of 18% PES, with the addition of varying concentrations of silica (1%, 2%, 3%, and 4%) and the membrane using the solvent N-Methyl- 2 Pyrrolidone (NMP) and Dimethyl Sulfoxide (DMSO). Membrane characterization was carried out by observing membrane morphology using Scanning Electron Microscopy (SEM), membrane surface functional group analysis test using Fourier Tranform Infrared (FTIR), membrane porosity test using the dry-wet weight procedure method, the highest porosity value was found on membrane B2 using a solvent DMSO with 2% silica is 16.88%. Membrane performance was carried out by pure water flux testing, the highest pure water flux value was found in membrane B2 with 2% silica, namely 64.14 L/m2.h. The antifouling test uses flux ratio recovery, the highest antifouling value is found on the A3 membrane with 3% silica, namely 91.3%. As well as rejection of the humic acid solution as a Natural Organic Matter (NOM) sample model using the ultrafiltration (UF) module with a dead end filtration flow system, the highest rejection value was found on the B2 membrane with 2% silica, namely 64.4%.